2018
DOI: 10.1093/annonc/mdy197
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide and irinotecan (TEMIRI regimen) as salvage treatment of irinotecan-sensitive advanced colorectal cancer patients bearing MGMT methylation

Abstract: TEMIRI regimen is a safe and active option in pre-treated, irinotecan-sensitive mCRC patients with MGMT methylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…Conversely, patients with non-hypermutated progressing lesions (TMB < 10 mutations/Mb) had increased MGMT expression compared to pre-treatment samples, suggesting that the selection and expansion of tumor subclones with MGMT expression may have played a crucial role in determining secondary resistance to temozolomide [84]. Similar findings were reported for another patient treated with the temozolomide plus irinotecan regimen [24]: post-progression tumor tissue displayed high TMB (68 mutations/Mb) in contrast to the pre-treatment sample (4 mutations/Mb). Despite increasing mutational load no somatic mutations in MMR repair were found with MSS status retained, and BRCA2 E2198* emerged likely as a passenger mutation.…”
Section: The Use Of Temozolomide As a "Priming" Therapy For Sensitizisupporting
confidence: 60%
See 2 more Smart Citations
“…Conversely, patients with non-hypermutated progressing lesions (TMB < 10 mutations/Mb) had increased MGMT expression compared to pre-treatment samples, suggesting that the selection and expansion of tumor subclones with MGMT expression may have played a crucial role in determining secondary resistance to temozolomide [84]. Similar findings were reported for another patient treated with the temozolomide plus irinotecan regimen [24]: post-progression tumor tissue displayed high TMB (68 mutations/Mb) in contrast to the pre-treatment sample (4 mutations/Mb). Despite increasing mutational load no somatic mutations in MMR repair were found with MSS status retained, and BRCA2 E2198* emerged likely as a passenger mutation.…”
Section: The Use Of Temozolomide As a "Priming" Therapy For Sensitizisupporting
confidence: 60%
“…An improvement of the efficacy of temozolomide may be expected from its use in earlier treatment lines and its combination with other agents with known activity in patients with mCRC. Considering this rationale, we ran an open-label, phase II non-randomized study on the combination of temozolomide plus irinotecan (TEMIRI), which showed promising and higher than expected activity [24]. Key inclusion criteria were: failure of at least two prior treatment lines including at least one prior irinotecan-based regimen, irinotecan-sensitive disease based on presence of an irinotecan-free interval (time from irinotecan last dose and disease progression) of 3 months or greater, presence of tumor MGMT methylation assessed by MSP and mismatch repair (MMR) proficiency.…”
Section: Improving the Efficacy Of Temozolomide In Patients With Metamentioning
confidence: 99%
See 1 more Smart Citation
“…Efficient DNA repair often confers poor response to chemotherapy and worse prognosis [79]. DNA-alkylating agents used in CRC therapy-such as temozolomide (treatment of metastatic CRC [132])-induce DNA lesions repaired by BER [132]. Suppression of the BER pathway by inhibiting polymerase β activity may also represent a tool for improving therapy response [133].…”
Section: Possible Utilization Of Oxidative Dna Damage In Colorectal Cmentioning
confidence: 99%
“…The limited single-agent activity of these drugs in the chemorefractory setting and the potential improvement of their efficacy when used in earlier treatment lines and/or in combination with other active agents represented the rationale for the design of temozolomide-based combination trials. For instance, in pretreated patients with irinotecan-sensitive disease (i.e., irinotecan-free interval >3 months), MGMT promoter methylation and MSS status, the combination of temozolomide with irinotecan (TEMIRI regimen) achieved a promising ORR of 24%-thanks to a potential synergy between the two agents (21). The CAPTEM regimen has been previously investigated in patients with metastatic, low-grade neuroendocrine tumors and showed manageable toxicity profile and promising efficacy (22).…”
Section: Discussionmentioning
confidence: 99%